Kuvitteellisia periferioita - Kuikka, Eeva (Idäntutkimus, 2021)
This article focuses on Nenets author Anna Nerkagi’s short novels Aniko of the Clan Nogo (1976) and The White Moss (1996) and their film adaptation The White Moss (2014) by Russian film director Vladimir Tumaev. I approach these works by asking how they depict the Arctic tundra as a space and how they describe the relationship between this peripheral space and the power centres. The main theoretical frameworks used are geocriticism and postcolonial theory. Nerkagi’s works depict the tundra as a region that is disconnected from the rest of the country and defined by Nenets history and the relationship with non-human nature. Especially in The White Moss, the reader can also notice a social critique of the neglect of the region. Tumaev’s film, on the other hand, relies on Russian cultural conceptions of the Arctic tundra and reflects Russia’s urge to be profiled as an Arctic superpower in the 2000s. Peer reviewed